Malaria Vaccines Methods and Protocols - Vaughan, Ashley.; Vaughan, Ashley. (Methods in Molecular Biology,, 2015)
This volume focuses on malaria vaccinology, and introduces researchers to a complete overview of the protocols and tools used by molecular and cellular malariologists. The chapters within this book talk about interventions concerning all aspects of life cycle progression--measuring antibody responses to blood stage parasite survival, the T Cell responses engendered by attenuated sporozoite vaccinations, and the unique effect on transmission of antibodies that target the mosquito stage of the life cycle. Additionally, methods concerning the ability to generate targeted gene deletions and replacements in the genome of Plasmodium parasites convey how Plasmodium parasite phenotypes can be created to precise specifications. More recently, the potential power of humanized mouse models of disease progression have been demonstrated and are also discussed in the book. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Cutting-edge and thorough, Malaria Vaccines: Methods and Protocols is a useful and unique resource for any aspiring malaria vaccinologists because of the volume's exquisitely detailed methodologies that are not typically found in published literature.  .